Study on the characteristics of head and neck movements of geese walking in a straight line at different speeds - Jiajia Wang; Zheng Zhang; Xinming Jiang; Dongyan Huang; Wei Song; Fu Zhang; Zhihui Qian; Lei Ren; Luquan Ren (Frontiers in Veterinary Science)
BackgroundThe avian cervical spine, a crucial anatomical structure connecting the cephalic and thoracic regions, serves a critical function in maintaining visual stability during locomotion. Extensive studies have documented characteristic head-bobbing behavior in small-bodied avian species (e.g., Columba livia domestica and Coturnix coturnix) during terrestrial movement. However, the kinematic patterns of Anser anser domesticus during ambulation across varying velocity parameters remain unexplored in current literature.ObjectiveTo investigate whether head bobbing occurs during head and neck movements; to analyze differences between head and neck movement characteristics under different walking speeds.MethodsHigh-speed photography equipment was used to obtain images of domestic geese in different linear walking states (slow walking, normal walking, and fast walking) and to analyze gait changes and head-neck movement characteristics under varying movement states.ResultThe results demonstrate that domestic geese exhibit nodding behavior similar to other birds, comprising thrust and hold phases. During a full nodding cycle, the thrust phase lasted significantly longer than the hold phase. Furthermore, the closer a goose's neck joint is to the trunk, the greater the joint angle variation observed across three motion states. This indicates that neck nodding depends on lower cervical joint motion. Concurrent analysis of head trajectories revealed horizontal stability during locomotion, with vertical fluctuation amplitude progressively decreasing as movement speed increased.